Pemberdayaan Kader Posyandu melalui SDIDTK dan PMT LokProhe untuk Pencegahan Stunting dan Penguatan Ekonomi Kreatif Berbasis Pangan Lokal: Empowering Posyandu Cadres through SDIDTK and PMT LokProhe to Prevent Stunting and Strengthen the Local Food-Based Creative Economy - Nelista, Yosefina; Fembi, Pembronia Nona; Syahrun, Muhammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Stunting remains a public health problem in Indonesia, with long-term impacts on the quality of human resources. Efforts to prevent stunting require targeted nutritional interventions and the active role of health workers. Integrated service post (Posyandu) cadres play a strategic role as the frontline in detecting, preventing, and addressing stunting. One strategy they can implement is to provide supplementary food made from local ingredients and animal protein. The purpose of this community service is to enhance the knowledge and skills of Posyandu cadres in implementing SDIDTK, completing KMS, and processing animal protein-based PMT as a step toward preventing stunting and boosting the creative economy. The methods used in this community service activity include outreach, training, technology implementation, mentoring, and evaluation of program success. The program targets 25 integrated health posts (Posyandu) cadres and will be implemented in Langir Village in September 2025. The results of statistical tests show that the knowledge and skills of cadres regarding SDIDTK, filling out KMS, PMT LokProhe, and marketing strategies increased significantly from the sufficient category (56%) to the good and skilled category (84%) after socialization and training. Therefore, the outreach and training provided effectively improved the knowledge and skills of Posyandu cadres. It is hoped that the cadres will effectively implement child growth and development simulations and utilize local foods, thereby improving their economic well-being.